2019
DOI: 10.1364/oe.27.006106
|View full text |Cite
|
Sign up to set email alerts
|

Frequency metrology of molecules in the near-infrared by NICE-OHMS

Abstract: Noise-immune cavity enhanced optical heterodyne molecular spectroscopy (NICE-OHMS) is extremely sensitive in detecting weak absorption. However, the use of NICE-OHMS for metrology study was also hindered by its sensitivity to influence from various experimental conditions such as the residual amplitude modulation. Here we demonstrate to use NICE-OHMS for precision measurements of Lamb-dip spectra of molecules. After a dedicated investigation of the systematic uncertainties in the NICE-OHMS measurement, the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Due to the relatively high Doppler broadening at these frequencies (4-5 × 10 −3 cm −1 ), a higher instrumental resolution is not sufficient to achieve a higher accuracy of the spectroscopic parameters. Such limitation can be overcome only in Doppler-free conditions, e.g., working in the saturation regime (Diouf et al, 2019;Hua et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the relatively high Doppler broadening at these frequencies (4-5 × 10 −3 cm −1 ), a higher instrumental resolution is not sufficient to achieve a higher accuracy of the spectroscopic parameters. Such limitation can be overcome only in Doppler-free conditions, e.g., working in the saturation regime (Diouf et al, 2019;Hua et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The FM of the probe laser sidebands is kept equal to the FSR of the CEAS cavity where an EOM can be utilized to create the sidebands. To minimize the fluctuations in the source laser, the laser is usually locked to the cavity through the PDH technique at a lower locking frequency than that for FM. , For further precision of the source laser frequency, it can be locked to an OFC . In certain cases, to reduce other background fluctuations such as etalon effects from optics, wavelength modulation with judicious selection of the modulation parameters can also be combined with NICE-OHMS .…”
Section: Optical Cavity-based Advanced Techniquesmentioning
confidence: 99%
“…To minimize the fluctuations in the source laser, the laser is usually locked to the cavity through the PDH technique at a lower locking frequency than that for FM. , For further precision of the source laser frequency, it can be locked to an OFC . In certain cases, to reduce other background fluctuations such as etalon effects from optics, wavelength modulation with judicious selection of the modulation parameters can also be combined with NICE-OHMS . It has also been demonstrated that the background noise in NICE-OHMS can be minimized by acquiring both the transmitted and the reflected signals from the cavity and taking a suitably weighted difference of the reflected from the transmitted signal .…”
Section: Optical Cavity-based Advanced Techniquesmentioning
confidence: 99%
“…The traceable high frequency electronic source referenced onto a GPS signal, provides a stable frequency that can be easily controlled which facilitates the cavity characterization. Although it is not generally the case for laser-based experiments, when using an electronic source, the finesse and the photon life time can be measured with the same setup without any additional complexity [28,29]. Once enough THz power has been injected into the FP cavity at a resonance frequency, the emitter is rapidly switched off, the exponential decay is recorded and the ring down time τR obtained.…”
Section: Thz Cavitymentioning
confidence: 99%